Pengaruh Manipulasi Laporan Keuangan dan Karakteristik Chief Financial Officer terhadap Ketepatwaktuan Pelaporan Keuangan dengan Kualitas Audit Sebagai Variabel Pemoderasi - Alif Hidayatullah; Sulhani Sulhani (Jurnal Dinamika Akuntansi dan Bisnis, 2018)
This study was conducted with the aim of obtaining empirical evidence of the relationship between financial statement manipulation and CFO’s characteristics to the timeliness of financial reporting by using audit quality as a moderator. The data used in this study is 206 observations derived from the financial statements of companies listed in the Indonesia stock exchange for the period of 2012-2015. This research uses moderation regression method with panel data. The manipulation of financial statements in this study was measured using the Benneish (M-Score) model, the characteristics of CFOs were measured regarding three categories consisting of gender, tenure and educational background, and audit quality was measured using industrial proxies of audit specialization. The results of this study support the first hypothesis that the manipulation of financial statements negatively affects the timeliness of financial statements. Meanwhile CFO’s characteristic has no significant influence on the timeliness of financial reporting and audit quality cannot moderate the influence of financial statement manipulation and CFO’s characteristic, hence it does not support another hypothesis of this study.